SOCIAL ENTREPRENEURS AS AN EFFORT IN IMPROVING MSME COMPETITIVENESS: A STUDY ON INDONESIAN KNITTING MSME CENTERS - Sulastri, Sulastri; Lisnawati, Lisnawati (Business Education Program of Universitas Pendidikan Indonesia, 2022)
: Competitiveness is the main concept whose application is very important for the progress and development of a company or MSME, businesses that do not pay attention and do not have competitiveness will automatically be abandoned by the market. MSMEs that have flexibility are seen as having great potential in supporting equity and economic welfare of the community. The Binong Jati Knitting MSME Center is one type of business from the goods supply sector in Indonesia which is indicated to be experiencing problems of low competitiveness. This study aims to determine the effect of social entrepreneurs on competitiveness. The method used is quantitative and the number of samples is 159 knitting entrepreneur s. The data analysis technique used is path analysis with SPSS version 25.0 computer software. The results showed that 1) leadership was at a good level, 2) strategy was at a good level, and 3) systems were at a good level. The influence of leadership 0.221 on competitiveness. strategy 0.150 on competitiveness, systems 0.140 on competitiveness, the influence of social entrepreneur 's on competitiveness is 51%, if seen from the Guilford table the total influence is in the medium classification. Based on the results of this study, it is suggested to entrepreneur at the Binong Jati Knitting MSME Center to increase the entrepreneur ial spirit that has a social entrepreneur vision. Especially in Leadership (Leadership) and Strategy (strategy) is accurate in increasing the effectiveness of business competitiveness